Shared auditors in private lending - Platikanova, P; Soonawalla, K (SAGE Publications, 2023)
We examine whether borrowers who share the same auditor with a syndicate lender (i.e., shared auditors) have improved access to the syndicate loan market. We predict and find evidence that shared auditors reduce information asymmetries between lenders and borrowers, as well as between lenders in a syndicate. We also find that borrowers who share auditors with lenders obtain better price and non-price terms compared to those without. Our empirical evidence also suggests that, when borrowers and lenders share auditors, syndicates are less concentrated and more diverse, consistent with the prediction that shared auditors provide informational benefits on the syndicate market. Loan facilities with shared auditors are also more likely to be renegotiated with more favorable terms for borrowers. Taken together, our findings suggest that shared auditors contribute to the efficient functioning of the debt market by reducing the information asymmetries in debt contracting.